THE EFFECTIVENESS OF ONLINE ASSESSMENT PLATFORMS IN EFL CLASSROOM: A STUDENTS' PERCEPTION ON USING KAHOOT APPLICATION - Ferri Hidayad; Umar Umar; Ariya Agustin; Despita Despita; Muhammad Bambang Purwanto (Sean Institute, 2023)
The purpose of this study is to evaluate Kahoot's efficacy as an online test and its effects on students' academic performance. 15 students from the management major were chosen as research participants by purposive sampling for this study at STIA Satya Negara. Utilizing a qualitative approach, this investigation. Interviews and questionnaires were the research tools used in this study. The purpose of the study's questionnaire was to learn how students felt about Kahoot as a digital evaluation tool used for in-class online quizzes. Additionally, interviews that were semi-structured were done to find out how lecturers and students felt about Kahoot as a digital evaluation tool. According to the study's findings, Kahoot is actually used in EFL lessons. According to the findings of the student impression survey, the majority of students more than 70% are happy with the Kahoot application. The academic success of students is enhanced with Kahoot. The progression of the daily and weekly quizzes demonstrates that student performance has greatly improved from the first week, midterm, to final semester exams.